Dietary Fiber Influences Bacterial Community Assembly Processes in the Gut Microbiota of Durco × Bamei Crossbred Pig - Tang, Xianjiang; Zhang, Liangzhi; Fan, Chao; Wang, Lei; Fu, Haibo; Ren, Shi’en; Shen, Wenjuan; Jia, Shangang; Wu, Guofang; Zhang, Yanming (Frontiers in Microbiology, 2021)
Several studies have shown that dietary fiber can significantly alter the composition and construct of the gut bacterial community in humans and mammals. However, few researches have been conducted on the dynamics of a bacterial community assembly across different graded levels of dietary fiber in different gut regions. To address this, 24 Durco×Bamei crossbred pigs were randomly assigned to four experimental chows comprising graded levels of dietary fiber. Results showed that the α-and β-diversity of the bacterial community was significantly different between the cecum and the jejunum. Adding fiber to the chow significantly increased the α-diversity of the bacterial community in the jejunum and cecum, while the β-diversity decreased. The complexity of the bacterial network increased with the increase of dietary fiber in jejunal content samples, while it decreased in cecal content samples. Furthermore, we found that stochastic processes governed the bacterial community assembly of low and medium dietary fiber groups of jejunal content samples, while deterministic processes dominated the high fiber group. In addition, deterministic processes dominated all cecal content samples. Taken together, the variation of gut community composition and construct in responding to dietary fiber was distinct in different gut regions, and the dynamics of bacterial community assembly across the graded levels of dietary fiber in different gut regions was also distinct. These findings enhance our knowledge on the bacterial community assembly processes in gut ecosystems of livestock.